A taxonomic review of the ant genus Megalomyrmex Forel (Hymenoptera: Formicidae) in Central America - Longino, John T. (Zootaxa, 2010)
The ant genus Megalomyrmex is known only from the Neotropics, where some of the species are specialized parasites or predators of Attini. A taxonomic review and a key to species is provided for the fauna of Central America and southern Mexico. The following new species are described: M. adamsae, M. mondaboroides, M. nocarina, M. reina.